Family members seeking compulsory hospitalization for drug-using members: profile, expectations and needs - Lorena Laiza Santana Veiga Silva; Jair Lourenço da Silva; Maria Goreti da Silva Cruz; Marcelo Geovane Perseguino; Ana Lúcia de Moraes Horta (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to outline the profile and understand the expectations and needs of family members who seek compulsory hospitalization for drug-using members. Method: Mixed research; data collected involving 101 medical records and semi-structured interviews with 26 family members. SPSS software and content analysis was used. Results: The sample was characterized predominantly by women. Most users had other treatment modalities. Significant associations were observed between the request for hospitalization, the presence of aggressiveness, and other behaviors typical of harmful drug use for requesting compulsory hospitalization. The categories were: The difficult coexistence with the user; the journey of family members to "bring the user back to life"; Expectations and needs regarding compulsory hospitalization. Conclusion: The study provided a broader view of the complexity and inter-subjectivities of family systems in the face of the drug cycle, promoting discussions and strategies for multidisciplinary services in the comprehensive care of these families.